Are Native and Nonindigenous Seaweeds Overgrowing Florida's East Coast Reefs? - Charles Jacoby; Brian Lapointe; LeRoy Creswell (EDIS)
SGEF-156, a 2-page illustrated fact sheet by Charles Jacoby, Brian LaPointe, and LeRoy Creswell, discusses the excessive growth of green macroalgae, or seaweed, on the reefs around Palm Beach Florida. It documents the observations and surveys of several plants in recent years, describes the ecological and economic consequences of macroalgal blooms, and urges readers to work to lower the amount of nutrients finding their way into coastal waters and avoid fueling macroalgal blooms. Published by Florida Sea Grant, University of Florida, IFAS Extension, June 2004.